2003
DOI: 10.1152/ajprenal.00266.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced changes in integrins and matrix-related functions in cultured human glomerular epithelial cells

Abstract: In cultured human glomerular epithelial cells (HGEC), 25 mM glucose resulted in decreased expression of alpha(3)-, alpha(2)-, and beta(1)-integrins and increased expression of alpha(5)- and alpha(v)beta(3)-integrins. This change was accompanied by decreased binding of HGEC to type IV collagen. In the presence of normal (5 mM) glucose concentration, cell binding to type IV collagen was primarily mediated by alpha(2)beta(1)- and alpha(5)beta(1)-integrins, as indicated by experiments in which cell adhesion to typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 48 publications
7
62
0
8
Order By: Relevance
“…Our data suggest that plasma MMP-2 (~70 kDa) is decreased in DKA, possibly due to the hyperglycemic conditions that are characteristic of DKA (25). Decreased MMP-2 facilitates increased extracellular matrix deposition in vascular structures as a primary function of MMP-2 is extracellular matrix turnover (26).…”
Section: Mmps In Pediatric Dkamentioning
confidence: 77%
“…Our data suggest that plasma MMP-2 (~70 kDa) is decreased in DKA, possibly due to the hyperglycemic conditions that are characteristic of DKA (25). Decreased MMP-2 facilitates increased extracellular matrix deposition in vascular structures as a primary function of MMP-2 is extracellular matrix turnover (26).…”
Section: Mmps In Pediatric Dkamentioning
confidence: 77%
“…It has been reported in streptozotocindiabetic rats, that the expression of α3β1 integrin, which is the main integrin occurring at the interface between the foot process and the GBM, was decreased in comparison to the normal control rate [9,10]. Accordingly, glomerular epithelial cells cultured in high glucose showed reduced expression of the α3, α2, and β1 integrin subunits in combination with increased expression of α5 and αvβ3 integrins [7]. An increase of the αv integrin subunit was also observed in situ, in podocytes in glomeruli of diabetic rats, compared to normal control rats [11].…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 92%
“…We have studied interactions between glomerular epithelial cells and their underlying matrix in vitro. In the presence of an increased glucose concentration (25 mM), the cells adhered less to collagen IV, a major component of the GBM, than glomerular epithelial cells grown at normal glucose concentration (5 mM) [7]. At normal glucose concentration, the interaction with collagen IV was mediated mainly by the α3β1 and α2β1 and to a lesser extent by α5β1 integrins, whereas at high glucose concentration the expression of αvβ3 and α5β1 integrins was upregulated ( Figure 2) [7,8].…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 97%
See 1 more Smart Citation
“…It was reported in literature that the expression of MMP-2 was decreased by 25mmol/L glucose, but the expression of TIMP-2, the special inhibitor of TIMP-1, was upregulated, which promoted ECM sidiment in the cultured human glomerular epithelial cells [5]. Berthier CC et al [6] found that the expression of MMP-2 and its inhibitor TIMP-2 and mRNA of TGF increased significantly in chronic rejection animal model of Fisher and Lewis mouse.…”
Section: Discussionmentioning
confidence: 99%